Appraisal Attitude in Ilaya Baxter’s Novel The Chameleons Among Us - Hasibuan, Rizky Ramadhani; Nurlela; Br. Perangin-angin, Alemina (Talenta Publisher, 2024)
This research aims to determine the types of Attitude and the realizations. It applied the Appraisal theory initiated by Martin and White (2005) regarding the types of Attitude contained in the text, the strength of the feelings involved, and ways of assessing that are sourced and aligned with the reader. It was conducted by using descriptive qualitative method and the data are the words, phrases, and clauses of the novel showing Appraisal Attitudes. The results showed that from 419 Sentences and 329 appraising items, dominantly there are 101 Attitudes of Positive Affect and 46 Attitudes of Negative Affect. Then, it is followed by 75 Attitudes of Positive Judgment and 41 Attitudes of Negative Judgment. Lastly, there are 50 Attitudes of Positive Appreciation and 16 Attitudes of Negative Appreciation. Also, it can be concluded that the realizations of Attitude can be shown by the emotions and feelings conveyed by each character in the novel to invite readers to understand the contents of the novel.